Role of JNK in a Trp53-Dependent Mouse Model of Breast Cancer - Cellurale, Cristina (Public Library of Science, 2010)
The cJun NH(2)-terminal kinase (JNK) signal transduction pathway has been implicated in mammary carcinogenesis. To test the role of JNK, we examined the effect of ablation of the Jnk1 and Jnk2 genes in a Trp53-dependent model of breast cancer using BALB/c mice. We detected no defects in mammary gland development in virgin mice or during lactation and involution in control studies of Jnk1(−/−) and Jnk2(−/−) mice. In a Trp53(−/+) genetic background, mammary carcinomas were detected in 43% of control mice, 70% of Jnk1(−/−) mice, and 53% of Jnk2(−/−) mice. These data indicate that JNK1 and JNK2 are not essential for mammary carcinoma development in the Trp53(−/+) BALB/c model of breast cancer. In contrast, this analysis suggests that JNK may partially contribute to tumor suppression. This conclusion is consistent with the finding that tumor-free survival of JNK-deficient Trp53(−/+) mice was significantly reduced compared with control Trp53(−/+) mice. We conclude that JNK1 and JNK2 can act as suppressors of mammary tumor development.